Inhibition of DAI refrains dendritic cells from maturation and prolongs murine islet and skin allograft survival - Cheng, Pengrui; Jian, Qian; Fu, Zongli; Deng, Ronghai; Ma, Yi (Frontiers in Immunology, 2023)
Introduction Central to allograft rejection is the T cell-mediated adaptive immune response initiated by activated dendritic cells (DCs). Previous studies have shown that the DNA-dependent activator of IFN regulatory factors (DAI) is involved in the maturation and activation of DCs. Therefore, we hypothesized that inhibition of DAI could prevent DCs from maturation and prolong murine allograft survival. Methods Donor mouse bone marrow-derived dendritic cells (BMDCs) were transduced with the recombinant adenovirus vector (AdV-DAI-RNAi-GFP) to inhibit DAI expression (DC-DAI-RNAi), and the immune cell phenotype and function of DC-DAI-RNAi upon lipopolysaccharide (LPS) stimulation were evaluated. Then DC-DAI-RNAi was injected into recipient mice before islet transplantation and skin transplantation. The survival times of islet and skin allograft were recorded and the proportions of T cell subsets in spleen and secretion levels of cytokines in serum were measured. Results We identified that DC-DAI-RNAi inhibited the expression of main co-stimulatory molecules and MHC-II, exhibited strong phagocytic ability, and secreted high levels of immunosuppressive cytokines and low levels of immunostimulating cytokines. Recipient mice treated with DC-DAI-RNAi had longer islet and skin allograft survival times. In the murine islet transplantation model, we observed an increase in Treg cells proportion, a reduction in Th1 and Th17 cells proportions in spleen, and similar trends in their secreted cytokines in serum in the DC-DAI-RNAi group. Conclusion Inhibition of DAI by adenovirus transduction inhibits the maturation and activation of DCs, affects the differentiation of T cell subsets as well as their secreted cytokines, and prolongs allograft survival.